UFC pay-per-view buys and the value of the celebrity fighter - Thomas R. Robbins; James E. Zemanek, Jr. (Innovative Marketing)
In 2016, the Ultimate Fighting Championship was sold for a reported price of $4 billion, the highest price ever paid for a sports franchise. This was a remarkable turn-around for a promotion that 15 years earlier was saved from bankruptcy by a $2 million buyout. This turnaround was driven by the UFC’s ability to mainstream the promotion and the sport while establishing reliable revenue streams through television contracts and massive pay-per-view events. In this paper, the authors review the pay-per-view record of the UFC and analyze the extent to which it is driven by high profile celebrity fighters with broad crossover appeal. Using statistical analysis, the authors identify the top crossover celebrities and assess the economic value they generate for the UFC. They compare this to the impact generated from the promotion’s highest ranked pound-for-pound fighter and find that celebrity has far more economic value than fighting skill.